Data mining in network traffic using fuzzy clustering - Mohamad, Shamsul (2003)
Nowadays, in network traffic, we have various application such as HfTP, Telnet, SMTP, FTP and NetBIOS. These various application make it difficult for the network administrator to model certain network traffic. The network traffic model is very important to know whether that particular network traffic is normal or abnormal. In this project, I have developed a program to capture and filter the packets based on the application. The fuzzy clustering process are made using three algorithms : Fuzzy C-Means (FCM), Gustafsof-Kessel (GK) and Gath-Geva (GG) algorithm. The production of clustering are used to build rules.